2014
DOI: 10.5455/njppp.2014.4.060520142
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity on cardiac autonomic functions in middle aged males

Abstract: Background: Obesity and health hazards associated with it are leading cause of death worldwide. The incidents of obesity are also rising at an alarming rate in the urban Indian population. Obesity is associated with adverse cardiovascular events which could be due to the altered autonomic balance seen in these individuals. Heart rate variability (HRV) is a non-invasive economical tool to assess the autonomic function. Aims & Objective: The present study was undertaken to evaluate the effect of obesity on heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…But resting heart rate was not varying in the both groups. Similar results were also observed by Anahita R Shenoy et al [8] in the age group of 40-55 years, Savas Sarikaya et al [9] in the 100 young age and sex matched patients, and Rajalakshmi et al [10] but their study was in younger population in the age group of 18-20 years. Chetan HA et al [11] have reported similar results in 20-24-year-old young Indian males, but their criteria for obesity classification (BMI > 30 kg/m 2 ) was different.…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…But resting heart rate was not varying in the both groups. Similar results were also observed by Anahita R Shenoy et al [8] in the age group of 40-55 years, Savas Sarikaya et al [9] in the 100 young age and sex matched patients, and Rajalakshmi et al [10] but their study was in younger population in the age group of 18-20 years. Chetan HA et al [11] have reported similar results in 20-24-year-old young Indian males, but their criteria for obesity classification (BMI > 30 kg/m 2 ) was different.…”
Section: Methodssupporting
confidence: 83%
“…The factors like age, gender and physical activity can also influence the HRV other than obesity [8]. In this study, age and sex matched 100 healthy middle aged obese and non-obese male individuals were participated (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased heart rate variability (both low and high frequency) has been observed in obese, compared to individuals with normal BMI [ 9 – 11 ]. Pockets of data available from Indian population are not different from those of western data [ 12 , 13 ]. However, India has an additional burden of chronic energy deficiency with one-third of population being of low BMI [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is one of the causes for majority of cardiovascular diseases. Obesity is an excess fat deposition of fat in the body individual (Shenoy et al, 2014) . Increased BMI also a risk factor for other some disease such as diabetes, stroke, osteoarthri-tis, respiratory dif iculties, etc.…”
Section: Introductionmentioning
confidence: 99%